Economic Contributions of the Forest Industry and Forest-based Recreation in Florida in 2016 - Christa Dean Court; Alan W Hodges; Mohammad Rahmani (EDIS, 2019)
The state of Florida is half woods, with 26,807 square miles of forestland. Our extensive natural and planted pine and hardwood forests are used for production of a wide variety of wood building materials, consumer paper and packaging products, chemicals, and renewable biomass fuels. In addition to industrial forest-related activity, public forestlands in Florida support a variety of recreational activities, attract a significant number of recreational visitors, and provide many non-marketed environmental or ecosystem services. This 4-page fact sheet written by Christa Dean Court, Alan W Hodges, and Mohammad Rahmani and published by the UF/IFAS Food and Resource Economics Department describes a study that analyzed the economic contributions of the forest industry and forest-based recreation activities to the state of Florida in 2016. http://edis.ifas.ufl.edu/fe1051